Analisis Perhitungan PPh Pasal 21 Karyawan Tetap Menggunakan Metode TER Pada PT Samudera Indo Perkasa - Geofany Marsela; Junawan (International Journal of Economics and Management, 2026)
The purpose of this thesis is to evaluate the Income Tax (PPh) Article 21 calculation mechanism for permanent employees at PT Samudera Indo Perkasa following the enactment of the latest regulation, PMK Number 168 of 2023 concerning the Average Effective Rate (TER). The research method used is descriptive quantitative and qualitative, with data collection techniques consisting of a literature review and documentation study of the company's Form 1721-A1 for 2025. This study focuses on two main aspects: the technical calculation procedure using TER categories A, B, and C, and the company's compliance level with applicable tax regulations. The results show that PT Samudera Indo Perkasa has correctly applied PMK 168/2023 by classifying permanent employee Prakash (K/2 status, PTKP Rp 67.500.000) under Category B TER, applying a 6.00% monthly effective rate from January to November 2025 with a total deduction of Rp9,900,000 and reconciling the final tax liability of Rp 9.975.000 in December using progressive rates under Article 17, resulting in a minor underpayment of Rp 75.000 that was properly adjusted.